Optical properties of the modified structures of surface layers of amorphous metallic alloy ribbons - Poperenko, L.V.; Kravets, V.G.; Lysenko, S.I.; Vinnichenko, K.L. (Functional Materials, 2006)
Modification of the microrelief and structure of a CO-based amorphous metal alloy ribbon surface layers after thermal treatment at elevated and cryogenic temperatures and under an external magnetic field has been studied using light scattering method and atomic force microscopy. The surface roughness parameters were calculated from the experimental light scattering indicatrices. It is shown that heating of the metal ribbons to Т - 350-475 ℃ relieves partially the stresses arising in the course of the ribbon prepara- tion and increases the surface roughness as compared to that of as-prepared samples. Модифiкацiя мiкрорельефа i структури поверхневих шарiв стрiчок аморфних сплавiв на основi CO пiсля термiчної обробки при пiдвищених та крiогенних температурах, пiд дiєю прикладеного магнiтного поля вивчена методом розсiяння свiтла i атомно-силовою мiкроскопiею. Параметри шорсткостi поверхнi розраховано iз експериментально отриманих iндикатрис iнтенсивностi розсiяння свiтла. Показано, що нагрiвання металевих стрiчок до Т = 350-475 ℃ частково знiмає напруження, що виникае пiд час виготовлення стрiчки, i пiдвищує шорсткiсть поверхнi порiвняно з тiєю, яка характерна для щойно виготовлених зразкiв. Модификация микрорельефа и структуры поверхностных слоев лент аморфных сплавов на основе Cо после термической обработки при повышенных и криогенных температурах, под действием приложенного магнитного поля изучена методом рассеяния света и атомно-силовой микроскопией. Параметры шероховатости поверхности лент рассчитаны из экспериментально полученных индикатрис интенсивности рассеянного света. Показано, что нагревание металлических лент до Т = 350-475 ℃ частично снимает напряжения, возникающие во время изготовления ленты, и повышает шероховатость поверхности по сравнению с той, которая характерна для свежеизготовленных образцов.